Active control of plasmonic colors: emerging display technologies. (15th January 2019) - Xiong, Kunli; Tordera, Daniel; Jonsson, Magnus P; Dahlin, Andreas B
Abstract: In recent years there has been a growing interest in the use of plasmonic nanostructures for color generation, a technology that dates back to ancient times. Plasmonic structural colors have several attractive features but once the structures are prepared the colors are normally fixed. Lately, several concepts have emerged for actively tuning the colors, which opens up for many new potential applications, the most obvious being novel color displays. In this review we summarize recent progress in active control of plasmonic colors and evaluate them with respect to performance criteria for color displays. It is suggested that actively controlled plasmonic colors are generally less interesting for emissive displays but could be useful for new types of electrochromic devices relying on ambient light (electronic paper). Furthermore, there are several other potential applications such as images to be revealed on demand and colorimetric sensors.